Testing a Theory of Change Model for Evaluating the Impact of Action Learning Programs - Karen E. Watkins; Aliki Nicolaides (Adult Education Research Conference, 2012)
This paper reports findings from an evaluation of an executive leadership development program in a large global healthcare organization. The paper offers a rethinking of evaluation from a transfer of learning model to a more open-ended, developmental approach based on a theory of change when learning is action-oriented, emergent, informal and incidental. Included in this paper are data from the evaluation illustrating learning increases in individual, group and system capacities to effectively engage with the demands placed on leaders and organizations in a complex, global context.